2015
DOI: 10.25077/jka.v4i1.207
|View full text |Cite
|
Sign up to set email alerts
|

102 Jurnal Kesehatan Andalas. 2015; 4(1) Pola Komplikasi Kronis Penderita Diabetes Melitus Tipe 2 Rawat Inap di Bagian Penyakit Dalam RS. Dr. M. Djamil Padang Januari 2011 - Desember 2012

Abstract: AbstrakDiabetes Melitus (DM) merupakan suatu kelompok penyakit metabolik dengan karakteristik hiperglikemia. DM tipe 2 adalah yang paling sering ditemukan. Komplikasi kronis DM tipe 2 yaitu mikrovaskular dan makrovaskular yang dapat menurunkan kualitas hidup penderita. Tujuan penelitian ini adalah untuk memperoleh gambaran tentang insidensi penderita DM tipe 2 dengan komplikasi kronis. Penelitian deskriptif ini dilakukan dengan mengambil data pada rekam medik penderita DM tipe 2 dengan komplikasi kronis yang d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…21 The collected data of complications profile is mostly dominated with single microangiopathy,Similarly,another previous researchfound the most common microangiopathy complication that occur in patients is diabetic nephropathy. 22 The dominating type of complications in this research is diabetic retinopathy as found in 46 respondents (22.6%). Similar to a research by Suryathi, among 123 respondents, 74 patients (60.16%) were diagnosed with diabetic retinopathy.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…21 The collected data of complications profile is mostly dominated with single microangiopathy,Similarly,another previous researchfound the most common microangiopathy complication that occur in patients is diabetic nephropathy. 22 The dominating type of complications in this research is diabetic retinopathy as found in 46 respondents (22.6%). Similar to a research by Suryathi, among 123 respondents, 74 patients (60.16%) were diagnosed with diabetic retinopathy.…”
Section: Resultsmentioning
confidence: 70%
“…Similarly, a research by Edwina, it was found that the most dominant complications was diabetic nephropathy found in 42.6% of respondents. 22 Nephropathy can be seen in microalbuminuria examination accompanied by glomerular filtration rate examination to assess patient's kidney function. Patients with a fast decreasing glomerular filtration rate may experience glomerulopathy and poor metabolic control.…”
Section: Resultsmentioning
confidence: 99%
“…Pasien diabetes melitus didapatkan 35-45% mengalami nefropati diabetik yang dapat berkembang menjadi gagal ginjal terminal (Pratama, 2013). Hasil penelitian Edwina, et al (2015)…”
Section: Pendahuluanunclassified
“…Diabetic complication, in this case nephropathy, is the leading cause of chronic kidney disease (CKD) and dialysis. 1,2 The prevalence of diabetic nephropathy is liable for the great issues on the healthcare systems worldwide. Medical costs have increased along with the progression of diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 99%